Acceptance of a flipped smart application for learning: a study among Thai university students. Issue 5 (4th July 2021) - Khlaisang, Jintavee; Teo, Timothy; Huang, Fang
ABSTRACT : This study investigated factors that influenced university students' intentions to use smart applications in flipped learning (FL) in Thailand flipped classrooms (FC) by extending the technology acceptance model (TAM) as the research model. Eight variables including relative advantage (ADV), peer influence (PI), school support (SS), reputation (REPU), innovativeness (INNO), facilitating conditions (FC), computer self-efficacy (CSE), and technological complexity (TC) were incorporated into the TAM to examine the relationships among these variables. Data were collected from 1339 students at 30 universities in Thailand using a self-report questionnaire and analyzed using structural equation modeling. The proposed model was found to have a good fit. The results of this study contributed to existing technology acceptance theories through indicating findings that are both consistent and inconsistent with previous studies. This study contributed to the understanding of FC/FL in Thai context. It could also inform national and school policymakers and educators of what university students think in terms of technological innovations used in higher education.